From observational to analytical morphology of the stratum corneum: progress avoiding hazardous animal and human testings - Piérard GE; Courtois J; Ritacco C; Humbert P; Fanian F; Piérard-Franchimont C (Dove Medical Press, 2015)
Gérald E Piérard,1,2 Justine Courtois,1 Caroline Ritacco,1 Philippe Humbert,2,3 Ferial Fanian,3 Claudine Piérard-Franchimont1,4,5 1Laboratory of Skin Bioengineering and Imaging (LABIC), Department of Clinical Sciences, Liège University, Liège, Belgium; 2University of Franche-Comté, Besançon, France; 3Department of Dermatology, University Hospital Saint-Jacques, Besançon, France; 4Department of Dermatopathology, Unilab Lg, University Hospital of Liège, Liège, Belgium; 5Department of Dermatology, Regional Hospital of Huy, Huy, Belgium Background: In cosmetic science, noninvasive sampling of the upper part of the stratum corneum is conveniently performed using strippings with adhesive-coated discs (SACD) and cyanoacrylate skin surface strippings (CSSSs). Methods: Under controlled conditions, it is possible to scrutinize SACD and CSSS with objectivity using appropriate methods of analytical morphology. These procedures apply to a series of clinical conditions including xerosis grading, comedometry, corneodynamics, corneomelametry, corneosurfametry, corneoxenometry, and dandruff assessment. Results: With any of the analytical evaluations, SACD and CSSS provide specific salient information that is useful in the field of cosmetology. In particular, both methods appear valuable and complementary in assessing the human skin compatibility of personal skincare products. Conclusion: A set of quantitative analytical methods applicable to the minimally invasive and low-cost SACD and CSSS procedures allow for a sound assessment of cosmetic effects on the stratum corneum. Under regular conditions, both methods are painless and do not induce adverse events. Globally, CSSS appears more precise and informative than the regular SACD stripping. Keywords: irritation, morphometry, quantitative morphology, stripping